The heart of a woman : the life and music of Florence B. Price - Brown, Rae Linda, 1953-2017 (Music in American life., 2020)
"Florence B. Price (1887-1953) was the first African American woman composer to achieve national recognition. She grew up in Little Rock, Arkansas, studies at the new England Conservatory, and spent her professional career in Chicago (1927-53), where her Symphony in E Minor, premiered by the Chicago Symphony Orchestra in 1933 under the direction of Frederick Stock, marks the first large-scale work by an African American woman composer (and the second work by an African American composer) to be performed by a major American orchestra. A prolific composer, she wrote more than 300 works in all genres: orchestra music (symphonies, orchestral suites, and concerti), vocal music, art songs and arrangements of spirituals, piano music (including teaching pieces), organ music, chamber music, and music for chorus. Her compositions reflect not only her cultural heritage, but also the romantic nationalist style of the period in which she was most active (beginning in the 1920s). Brown discusses Price in the context of the Harlem Renaissance and deals with issues of race, gender, and class. She draws on interviews with Price's colleagues, on music manuscripts located in major repositories of African American material and in private collections, on contemporary black newspapers and journals, on census records, and on archival materials as well as the relevant published sources. An appendix lists Price's compositions by genre"--